International Monetary Fund Annual Report 2018 : Building a Shared Future. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2018)
The past year was one of growing economic anxiety tied to skepticism about both economic integration and an international approach to economic policy making. To help make globalization work for all, the IMF focused on providing policy advice in many macro-critical areas.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet